Estratégias Corporativas: um estudo de caso na Holding CVI - Santa Maria - Fratton, Roberto (2006)
The present research, which treats about the development of Corporate Strategics, was done at Holding CVI, with home office in Santa Maria-RS city. The Holding CVI, that among others investments, works on beverage area, has as its main business, The Coca Cola Company franchise, in the region of Santa Cruz do Sul, Passo Fundo and Santa Maria, cities located in Rio Grande do Sul. This research is case a study, and has as its goal suggesting to the stockholder the development of Strategics Alliances - merging, purchases an associations that allow the grow of the Holding. To the conception of this Strategics Alliances it takes into consideration the followings points: the company historic, the environment analyze of beverage field and the stockholder profile.